Design of a conceptual model for manufacturing companies within the 4th industrial revolution applying the Viable System model. Issue 1 (October 2021) - Gallego, S; García, M
Abstract: The initiative created under the name "Industry 4.0" in 2011 [3] can help to strengthen the competitiveness of those manufacturing companies [4] able to adapt themselves to this fourth wave of technological advancement driven by various technological advances [5]. Most manufacturing companies have developed departments and initiated projects around the concept Industry 4.0. However, many of them lack the purpose, the organizational acceptance, and the alignment of those activities with the organization´s strategy. Therefore, the aim of this research is to design a conceptual model for improving organizational capabilities thanks to industry 4.0. For this development, the Viable System Model (VSM) was selected as methodological approach. The conceptual model determines the relations between technical areas, technologies, and organizational strategy. The model for Industry 4.0 can help manufacturing companies serving as a guidance for future organizational structure, projects, and activities selection as well as to determine areas with higher potentials according to the status of its technologies and their related current and future capabilities.